Traffic Unit E-TLE Implementation to Reduce Accident Numbers in the Jurisdiction of the Jombang Police - Jovian, Adrian (Advances in Police Science Research Journal, 2024)
This research is motivated by the high number of traffic accidents in Jombang Regency. The numerous traffic violations committed by the public are one of the initial causes of traffic accidents. Such conditions require an extra role from the Police to enforce the law when preemptive and preventive measures are ignored by the public. Enforcement can be done by imposing administrative sanctions (fines), where the implementation of fines themselves has become increasingly modern following technological developments, namely through the E-TLE program, which has been officially launched by the National Traffic Corps (Korlantas Polri). This study employs the concepts of fines, law enforcement, and traffic violations, utilizing George R. Terry's Management Theory and the Deterrence Effect theory as analytical tools. It adopts a qualitative approach and descriptive method to explain the implementation of the E-TLE program in enforcing traffic violations to reduce accident rates in Jombang Regency. Data sources were obtained through interviews, observations, and document reviews. The research findings indicate that the situation of traffic safety and order (kamseltibcar) is still inadequate, marked by continuously increasing traffic accident rates. Furthermore, the implementation of law enforcement with E-TLE still faces shortcomings such as insufficient training for personnel, limited E-TLE facilities and infrastructure, and implementation challenges in certain areas. Factors affecting the implementation of the E-TLE program include internal factors such as personnel capabilities, attitudes and ethics, facilities and infrastructure, budget, methods, as well as external factors such as nature and environment, community, and cooperation with other agencies. Recommendations from the researcher for future improvements in E-TLE implementation include providing E-TLE training for all traffic personnel, increasing E-TLE equipment and infrastructure, and enhancing coordination and collaboration between the police and relevant agencies to improve traffic safety and order through the E-TLE program, thus ensuring more effective implementation of the E-TLE program.